2015
DOI: 10.1007/978-3-319-16006-1_25
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Regional Change—Land Cover

Abstract: Anthropogenic land-cover change (ALCC) is one of the few climate forcings for which the net direction of the climate response over the last two centuries is still not known. The uncertainty is due to the often counteracting temperature responses to the many biogeophysical effects and to the biogeochemical versus biogeophysical effects. Palaeoecological studies show that the major transformation of the landscape by anthropogenic activities in the southern zone of the Baltic Sea basin occurred between 6000 and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 122 publications
(166 reference statements)
0
5
0
Order By: Relevance
“…Krug et al (2015) concluded that there were regional differences in how the vulnerability and productivity of forestry systems were affected by climate change, with the southern and eastern parts of the Baltic Sea region likely to experience reduced production and the northern and western parts increased production. Gaillard et al (2015) found no indication that deforestation in the Baltic Sea region since 1850 could have been a major cause of the observed climate warming.…”
Section: Previous Assessmentsmentioning
confidence: 86%
See 2 more Smart Citations
“…Krug et al (2015) concluded that there were regional differences in how the vulnerability and productivity of forestry systems were affected by climate change, with the southern and eastern parts of the Baltic Sea region likely to experience reduced production and the northern and western parts increased production. Gaillard et al (2015) found no indication that deforestation in the Baltic Sea region since 1850 could have been a major cause of the observed climate warming.…”
Section: Previous Assessmentsmentioning
confidence: 86%
“…In the second BACC report (BACC II Author Team, 2015), climate effects on terrestrial ecosystems were less in focus, with a section related to forests and natural vegetation in the chapter on environmental impacts on coastal ecosystems, birds and forests (Niemelä et al, 2015) and as part of the chapter on socioeconomic impacts on forestry and agriculture (Krug et al, 2015). On the other hand, the second BACC report also considered anthropogenic land-cover changes as a driver of regional climate change (Gaillard et al, 2015). Niemelä et al (2015) concluded that the observed positive effects of climate change on forest growth would continue, in particular for boreal forest stands that benefitted more than temperate forest stands.…”
Section: Previous Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…20–30% or more), the REVEALS results have major consequences on our understanding of the anthropogenic impact on land cover (landscape openness/deforestation in particular) and, in turn, on the possible effects of anthropogenic land‐use change on climate (e.g. Strandberg et al ., ; Gaillard et al ., , in press).…”
Section: Discussionmentioning
confidence: 99%
“…Although landscape management is expected to play a large role in the mitigation of climate warming in the future (Nabuurs et al, 2022), the local impact of such mitigation measures on the regional climate and the net effect of both biogeochemical and biogeophysical effects, in the past as well as today, are still not fully understood or known (e.g. Gaillard et al, 2015). The relative importance of LULCC as a climate forcing factor may be large, particularly in lowemission scenarios (van Vuuren et al, 2011).…”
Section: Introductionmentioning
confidence: 99%